A time preference measure of the social discount rate for Iran - Arian Daneshmand; Esfandiar Jahangard; Mahnoush Abdollah-Milani (Journal of Economic Structures, 2018)
Public sector projects in Iran are inefficiently carried out for reasons of mismanagement and poor prioritization. This problem may arise from the lack of a generally accepted social discount rate for project appraisal. The value of the social discount rate can have implications for resource allocations. The aim of this paper is to estimate the appropriate value of a social discount rate for Iran using the social time preference rate approach. The overall result indicates that the social discount rate for Iran is 5.8%.
Keywords: C32; H43; 330; Social discount rate; Social time preference rate; Project appraisal; ARDL; Iran